Evaluation of the Implementation of the Strategy of Social and Economic Development of Territorial Communities in the Context of Achieving Sustainable Development Goals - Nadiia Pylypiv; Svyatoslav Sologub (Journal of Vasyl Stefanyk Precarpathian National University)
The purpose of the article is to substantiate the theoretical and methodological provisions and develop practical recommendations for improving the evaluation of the implementation of strategies for the social and economic development of territorial communities in the context of achieving the goals of sustainable development. To evaluate the implementation of strategies for the social and economic development of territorial communities, the author proposes to use the Balanced Scorecard (BSC) as an effective economic tool for strategic planning by setting strategic goals in selected blocks using selected target indicators, both financial and non-financial. The article proposes, in the context of achieving the sustainable development goals, to form the following BSC blocks for territorial communities: financing, service providers, service consumers, environment, and cooperation, which have their own characteristics and differ significantly from the four blocks of enterprises: internal processes, finance, training and growth (personnel), and customers interacting with each other. At the same time, the indicators selected for assessing these blocks have appropriate interrelationships and provide the necessary analytical information to achieve the strategic goals of the communities. To ensure the effectiveness of the assessment of the implementation of strategies for the social and economic development of territorial communities, the BSC system was systematized, and a matrix of correspondence between strategic directions and goals for the Broshniv-Osad Territorial community and the BSC was created. This helps to structure information about the selected strategic guidelines of the community and facilitates the further selection of key BSC indicators, which made it possible to link the strategic goals of the territorial community with the BSC blocks and the identified targets in order to choose a reasonable solution in the context of successful achievement of the goals of sustainable development not only of a separate territorial community but also of the country as a whole.